Inflammation in the Pathogenesis of Arrhythmogenic Cardiomyopathy: Secondary Event or Active Driver? - Meraviglia, Viviana; Alcalde, Mireia; Campuzano, Oscar; Bellin, Milena (Frontiers in Cardiovascular Medicine, 2021)
Arrhythmogenic cardiomyopathy (ACM) is a rare inherited cardiac disease characterized by arrhythmia and progressive fibro-fatty replacement of the myocardium, which leads to heart failure and sudden cardiac death. Inflammation contributes to disease progression, and it is characterized by inflammatory cell infiltrates in the damaged myocardium and inflammatory mediators in the blood of ACM patients. However, the molecular basis of inflammatory process in ACM remains under investigated and it is unclear whether inflammation is a primary event leading to arrhythmia and myocardial damage or it is a secondary response triggered by cardiomyocyte death. Here, we provide an overview of the proposed players and triggers involved in inflammation in ACM, focusing on those studied using in vivo and in vitro models. Deepening current knowledge of inflammation-related mechanisms in ACM could help identifying novel therapeutic perspectives, such as anti-inflammatory therapy.